Micronutrient Deficiency in Children and Adolescents with Obesity-A Narrative Review - Valeria Calcaterra; Elvira Verduci; Chiara Milanta; Marta Agostinelli; Carolina Federica Todisco; Federica Bona; Jonabel Dolor; Alice La Mendola; Martina Tosi; Gianvincenzo Zuccotti (MDPI AG, 2023)
Childhood obesity represents a serious public health burden. Despite excessive dietary consumption, children with obesity present high rates of micronutrient deficiencies, such as deficiencies in minerals and specific vitamins; micronutrient deficiencies may have a pathogenic role in obesity-related metabolic comorbidities. In this narrative review, we analyzed the main deficiencies associated with obesity, their clinical consequences, and the evidence about a possible supplementation. Iron; vitamins A, B, C, D, and E; folic acid; zinc; and copper deficiencies represent the most common deficient microelements. The relationship between obesity and multiple micronutrient deficiencies remains unclear, and different mechanisms have been proposed. The medical care plan for pediatric obesity should include food choices with high nutritional content as part of a crucial approach to obesity-related complications. Unfortunately, only a few studies are available regarding the efficacy of oral supplementation or weight loss for treating them; thus, continuous nutritional monitoring is necessary.